Improve Vocabulary Writing Skills through Image and Image Models on Indonesian Language Maples - Desi Anggar Pratiwi (Universitas Sebelas Maret, 2020)
The purpose of this study was to improve vocabulary writing skills in grade II SDN Wukirsari students through the application of the Picture and Picture model assisted by google meet. The research conducted was a Classroom Action Research (PTK) with three cycles, with each cycle consisting of two meetings. The stages of each cycle are planning, implementing, observing and reflecting. Each meeting is carried out a pre test and post test to determine the progress of students. In the first cycle students who completed after carrying out the post test were 50%. In cycle II students who completed after carrying out the post test were 80%. These results indicate that the Picture and Picture learning model can improve student learning outcomes, especially Indonesian language muples at SD Negeri Wukirsari.